Efficacy of intermittent versus daily vitamin D supplementation on improving circulating 25(OH)D concentration: a Bayesian network meta-analysis of randomized controlled trials - Zhuang, Yan; Zhu, Zhe; Chi, Peihan; Zhou, Haibo; Peng, Zhicheng; Cheng, Haoyue; Xin, Xing; Luo, Wenliang; Si, Shuting; Mo, Minjia; Chen, Danqing; Liu, Hui; et al. (Frontiers in Nutrition, 2023)
Background: Vitamin D deficiency is a widespread issue globally, resulting in increased use of vitamin D supplements. However, it is unclear whether intermittent (weekly or monthly) vitamin D supplementation is as effective as daily supplementation in improving circulating 25-hydroxyvitamin D [25(OH)D] levels. Methods: Three databases including Medline, EMBASE, and Cochrane Library were systematically searched up to Nov 10, 2020. Risk of bias was evaluated according to Cochrane Collaboration's tool for rating methodological quality assessment. Direct and indirect comparisons between interventions and controls were performed by a Bayesian network meta-analysis (NMA), where mean difference (MD) and its 95% confidence interval (CI) was used to indicate the efficacy. Results: This NMA analysis included 116 RCTs with a total of 11,376 participants. Generally, we observed 25(OH)D concentrations were significantly elevated regardless of vitamin D supplementation frequency. Although the findings of SUCRA indicated that daily vitamin D supplementation had a higher rank value than intermittent supplementation when the supplement dosage was similar, no statistically significant pooled mean differences of 25(OH)D concentration were noted between daily supplementation group and intermittent supplementation group. Additionally, weekly supplementation with a total of 600,000 IU vitamin D supplementation during three months had the best efficacy in elevating 25(OH)D concentration (pooled MD=63 nmol/L, 95%CI: 49-77). To achieve optimal 25(OH)D concentration (>75 nmol/L), we recommended 60,000 IU vitamin D supplementation monthly (~2000 IU/day). Conclusion: To sum up, the efficacy of intermittent vitamin D supplementation was similar to daily supplementation. Coupled with its convenience, frequency and dosage of intermittent vitamin D supplements were recommended to reach optimal 25(OH)D 4 level.Review registration: PROSPERO CRD42021257257.